Pengaruh Penerapan Shalat Dzuhur Berjamaah dan Mengaji Al-Qur’an Terhadap Karakter Siswa di Ponpes Darul Hikmah - Nor Istiana; Rizqiyah; Junaidi (SYAIKHONA: Jurnal Magister Pendidikan Agama Islam, 2024)
Good student character is formed by sincerity and a sense of responsibility for students supported by teacher activity as the main support. The success of building good character certainly does not escape from the spiritual good deeply towards the students themselves. The importance of providing direction as well as direct knowledge and practice makes students more quickly understand and follow these habits so that they stick to character in students. This research method uses quantitative methods that aim to produce findings from objectives based on statistical procedures with quantitative measurements collaborated on multiple linear regression analysis methods with SPSS applications. The population in this study was students in Ponpes Darul Hikmah Langkap, Burneh, Bangkalan with a sample of 33 students. The purpose of the study was to determine how much influence the application of congregational dzuhur prayer and Qur'an recitation on the character of students at PonPes Darul Hikmah. The results showed that: (1) There was no significant influence between congregational dzuhur prayers on building the character of students at PonPes Darul Hikmah Langkap Burneh Bangkalan. Which is shown from tcount > ttable (0.186≤ 1.965).  (2) There is no significant effect between reading the Qur'an on building student character as shown from thitung > ttabel (0.287≤ 1.965). (3) There is no significant influence between congregational prayer and Qur'an reading on building student character as shown from Fhitung (0.141) > Ftabel (2.52), the number of squre which explains that the congregational prayer and reciting the Qur'an (X) to the character of the student (Y) is 0.009 (9%) and the rest is influenced by other variables.